Web rules how the Internet is changing the way consumers make choices - Murphy, Tom 1953- (Dearborn, 2000)
In the Web world, nothing will ever be the same. The Internet is changing the balance of power between consumers, the companies they buy from, and the social and political institutions they interact with. Corporations and institutions have only a small window in which to learn new rules of engagement, or risk being barred from the game. Veteran technology journalist Tom Murphy forecasts the changes to come in shopping, finance, media, healthcare, entertainment, and gadgetry. Supplementing his informed predictions are conversations with visionary business leaders such as Barry Diller, Andy Grove, and Jerry Yang.